The Moderating Effect Of Age In The Relationship Between E-Goverment Services And Job Performance On Civil Status And Passport Department In Jordan - Khaled Mahmoud Jalil Almashaqbeh
Governments are trying to develop performance through using e-government services, but there are some obstacles that affect the achievement of this goal. This study aimed to investigate the moderation effect of age in the relationship between e-government services and job performance on Civil Status and Passport Department (CSPD), Jordan. Data were collected from front-line employees in the Jordanian CSPD. A closed; Likert scale questionnaire was used to collect data. A sample of 400 front-line CSPD employees was selected randomly and 335 were used for subsequent analysis. The statistical package of social science (SPSS) program was used to conduct factor analysis, reliability analysis and descriptive statistical analysis and the AMOS program was used to carry out the structural equation modeling as well as examining the research hypotheses. The analysis and models verified the hypothesis, where it was mentioned that there is interdependence in the independent variable (e governance) and the moderator (age) of this research but the dependent variable (job performance) and the moderator are not interconnected if we consider the relationship of age and job performance. It could be concluded that this study extended the understanding of the factors that influence the usability of governmental e-services to enhance the performance of employees. These factors received considerable attention from both employees and governmental organizations perspectives. The findings recommend more attention should be paid on management strategies related to consider technology adoption and implementation to enhance employees’ job performance through the significant differences among the age groups.